Four-component defluorinative reaction of allylic fluorides, amidines, and Cs2CO3 under transition-metal-free conditions. Issue 18 (22nd August 2022) - Chen, Yu-Lan; Sun, Li-Wen; Chen, Jia-Wei; Zhu, Ming-Quan; Ma, Mengtao; Shen, Zhi-Liang; Chu, Xue-Qiang
Abstract : An unprecedented four-component defluorinative reaction of allylic fluorides, amidines, and Cs2 CO3 for the convenient synthesis of valuable pyrimidine-containing amidino carbamates under transition-metal-free conditions was developed. Abstract : Research interest in defluorinative functionzalization by means of the distinctive fluorine effect of organofluorides has led to rapid development in this topic. Herein, we reported an unprecedented four-component defluorinative reaction of allylic fluorides, amidines, and Cs2 CO3 for the convenient synthesis of valuable pyrimidine-containing amidino carbamates under transition-metal-free conditions. The synthetic linchpin for realizing the multi-bonding tandem protocol relied on the directed function of the α-positioned hydroxyl group and the activating effect of the perfluoroalkyl substituent in allylic fluorides. Moreover, cesium carbonate served as a green carbonyl equivalent for formal CO capture. Mechanistic studies revealed that the reaction proceeded via a possible cyclic carbonate intermediate.